Prototyping Mass Nouns from Students’ Perspective: A Pedagogical Implication - Alam, Md (Advances in Social Sciences Research Journal, 2020)
This paper investigates ESL learners’ prototyping mass nouns as a grammatical category. The study is supported by the theory of prototype developed by Rosch in 1970s which plays a wide role in graded categorization of the existent entities in the world. With an expected inspiration from the theory, the prototyping of vocabulary received research attention especially in the pedagogical world. Promisingly, this study seeks to extend the theory to explore a lexico-grammatical category i.e. “mass nouns” from learners’ perspective. Actually, the study was directed to find out which prototypical feature ESL students exploit to prioritize some mass nouns as prototypical examples over some other mass nouns, and how far students’ experientially and pedagogically perceived “prototypes” of mass nouns help them to correctly grouping up nouns as in mass category. The study was focused on shedding some light on a few pedagogical tips and implications in some likely challenging contexts of teaching mass nouns. The study reveals that ESL students shortlist ‘liquids’ (such as water, milk, wine, juice etc.) ‘gases’(such as hydrogen, oxygen etc.), ‘abstract ideas’ (such as childhood, anger, safety, knowledge etc.), ‘powdered substances’ (such as sand, sugar etc.), and some ‘natural entities’ (such as heat, sunshine etc.) as “prototype of mass nouns” which all are un-individuated and sometimes intangible - meaning uncountable - while the learners recognize ‘non-countable’ status as the most important prototypical feature of mass nouns. And, the students isolated ‘rice’, ‘wheat’, ‘hair’, ‘grass’ , ‘cotton’ and ‘coal’ as less prototypical mass nouns based on their intrinsic sense that these mass nouns are plural and they even can be individuated. However, the study reflects that the students’ perceived prototypes are not sufficient as they selected and considered many of mass nouns as so distant members as countable. It was further found that contextual type shifts of mass-count nouns, arbitrary sematic distributions to lexis, cross-linguistic approach to mass nouns, intrinsic and realistic conception, superordinate-subordinate influence, and perception of enumerating status etc. account for students’ this surprise selection of a number of mass nouns as opposite category i.e. count nouns. If pedagogues are non-responsive to these factors and fail to redefine their approaches to mass noun teaching, it is most likely to lead to learners’ grammatical inaccuracy resulted from their determiner-number-mass noun mismatch.